Rights of inclusion law and identity in the life stories of Americans with disabilities - Engel, David M.; Munger, Frank (Chicago : University of Chicago Press, 2003)
David M. Engel and Frank W. Munger argue for a radically new understanding of rights - one that focuses on their role in everyday lives rather than in formal legal claims. Although all 60 interviewees had experienced discrimination, none had filed a formal protest or lawsuit. Nevertheless, civil rights played a crucial role in their lives.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: People with disabilities -- Civil rights -- United States; People with disabilities -- Legal status, laws, etc. -- United States; Discrimination against people with disabilities -- Law and legislation -- United States; People with disabilities -- United States -- Biography; Law; United States of America, USA; Disability: social aspects; Politics & government; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law